Toxic effects of dioxins on the human body - Sarnowska, Marta; Gach, Sonia (Journal of Education, Health and Sport, 2017)
Dioxins have been attended the humanity since the dawn of time but developments of civilization has increased the concentration of these substances in the environment while simultaneously driving the development of many diseases associated with harmful environmental pollutants. Due to the specificity of its structure, dioxins are difficult to remove during the biodegradation process. The awareness of the governmental authorities in many countries on the subject of harmful effect of dioxins in humans has led to the introduction of stricter legislation contained in the Stockholm Convention Reports and in the National Legislation related to the control and reduction of emissions to the environment of persistent organic pollutant (POPs), which also include dioxins. The International Agency for Research on Cancer (IARC) has listed a group of these compounds, which also include dioxins, to carcinogens group A, however, despite the fact that the risk of dioxin poisoning is enormous, the knowledge of environmental and health problem is small in society.